THE INFLUENCE OF INFORMATION TECHNOLOGY AND MEDIA WEB-BASED LEARNING ON EFFECTIVENESS LEARNING ADMINISTRATIVE EDUCATION STUDENTS OFFICE 2023 - tias, wuri (Journal of Education and Teaching, 2025)
This study aims to investigate the influence of information technology and web-based learning media on the learning effectiveness of office administration education students in 2023. The findings show that there is a significant positive effect of information technology and webbased learning materials on learning effectiveness. The analysis reveals that the use of webbased media and technological tools improves students' understanding and attention during the learning process, creating a dynamic and responsive learning environment that meets their needs. Additionally, the technology facilitates better engagement and retention among students, ultimately contributing to improved overall academic performance. Therefore, this study emphasizes the importance of integrating sophisticated digital resources into the educational environment to improve pedagogical outcomes.